ENT pathologies screening in woodworkers in Parakou, Benin - HOUNKPATIN, Spéro; GOUNONGBE, FABIEN; LAWSON ÉPSE AFOUDA, SONIA RUTH JOSÉPHINE; FLATIN, Marius; DOSSOU KPANOU, Karl; AVAKOUDJO, FRANÇOIS; DOSSOUMOU, Elvire; ADJIBABI, WASSI (My University, 2014)
.........
Keywords: Timber; wood workers; occupational rhinitis; ENT pathologies